Macro vs. micro methods in non-life claims reserving (an econometric perspective) - Arthur Charpentier; Mathieu Pigeon (Risks, 2016)
Traditionally, actuaries have used run-off triangles to estimate reserve ("macro" models, on aggregated data). However, it is possible to model payments related to individual claims. If those models provide similar estimations, we investigate uncertainty related to reserves with "macro" and "micro" models. We study theoretical properties of econometric models (Gaussian, Poisson and quasi-Poisson) on individual data, and clustered data. Finally, applications in claims reserving are considered.
Keywords: 330; loss reserving; clustering; generalized linear mixed models